Rhinitis is also Common in Infants with Asthma - Herberto José Chong Neto (Iranian Journal of Allergy, Asthma and Immunology, 2010)
The aim of this study was to assess the frequency of rhinitis in asthmatic infants. A cross-sectional study was conducted using clinical data obtained from a standardized allergy work-up form that includes specific questions on common allergic diseases. Asthmatic patients were seen at the first visit to the Pediatric Allergy Unit, from January 2001 to January 2006, were selected for analysis. Diagnosis of allergic rhinitis was based on the presence of two or more nasal symptoms (sneezing, itching, congestion and rhinorrhea). Allergic sensitization was assessed by skin prick test for Dermatophagoides pteronyssinus, Blomia tropicalis, Blattella germanica, Lolium perenne, dog and cat danders. Four hundred and ninety-three infants (under 2 years of age) were selected from a total of 1543 asthmatics aged 0-14 years, 58% males. Physician diagnosis of rhinitis in infants was registered in 367 (74%) and 131 (36%) had positive skin prick test to at least one allergen. Infants were more frequently sensitized to Dermatophagoides pteronyssinus (43%) and Blomia tropicalis (27%). Among asthmatic children ≥2 years old, 890 (84%) also had rhinitis, 773 (87%) were atopic. Among those children with rhinitis, one hundred and eighty six were fully skin prick tested with a standard panel of common aeroallergens. There was no difference between sensitization in asthmatic infants and older asthmatic children with allergic rhinitis. Thus the frequency of rhinitis in asthmatic infants as well as atopic sensitization were similar to older children.